Dropping out – Hungarian experiences at vocational training - Csehné Papp, Imola; Héder-Rima, Mária; Dajnoki, Krisztina (Acta Medicinae et Sociologica, 2021)
The proportion of people with low school qualifications remains significant in Hungary, which not only makes it difficult for them to enter the current labour market but may also exclude them in the long term. For the increasing number of people with a low level of education, dropping out seems to be one of the most common reasons. Prevention as a determinative measure can provide answers to this problem. The study focuses on the issue of secondary school drop-out. The study results were based on the methodology of questionnaire surveys and semi-structured conversations. Based on the information obtained from the survey, this study continuously presents the results connected to drop-out conditions and compensatory measures. The study results highlight the significant effects of school and family, including previous school experiences, influence on the place of residence, the labour market status. The conclusions drawn from the results address the topic in a practical way and provide an opportunity to develop a possible action plan to prevent drop-outs.